PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, CEO DUALITY, PROFITABILITAS, LIKUIDITAS, LEVERAGE, SALES GROWTH, DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR AGRIKULTUR YANG TERDAFTAR DI BEI PERIODE 2017 - 2021 - Mayang Putri; Achmad Kautsar (Jurnal Ilmu Manajemen, 2023)
This research aims to determine the effect of institutional ownership, managerial ownership, CEO duality, profitability, liquidity, leverage, sales growth, and firm size on financial distress in agricultural sector companies listed on the Indonesia Stock Exchange for the 2017 – 2021 period. The type of data used is quantitative data sourced from secondary data. This research's population are companies in the agricultural sector listed on the Indonesia Stock Exchange from 2017-2021. The sample retrieval technique used saturated samples and obtained 16 companies as samples in this research. The data were analyzed using logistic regression and calculated with IBM SPSS 26. The results showed that a CEO duality significantly and positively affected financial distress. Profitability proxied by return on asset particularly and negatively impacted financial distress. While institutional ownership, managerial ownership, liquidity (current ratio), leverage (debt to asset ratio), sales growth, and firm size do not significantly affect financial distress. Therefore, companies in the agricultural sector cannot implement a CEO duality system with a kinship system because it can put the company a probability of financial distress. Agricultural sector companies must also give more attention and increase the value of return on assets to avoid financial distress.